Predicting Outcomes in Posterior Lumbar Interbody Fusion Surgery Using the Kaplan-Feinstein Comorbidity Index - Rahman, Md Moshiur; Khan, SIM Khairun Nabi; Khan, Robert Ahmed; Khan, Bashir Ahmed; Hasan, Md Mahbub; Chowdhury, Muhtamim; Habib, Riad (Bangladesh Journal of Neurosurgery, 2026)
Objective: This study evaluates the predictive value of the Kaplan-Feinstein Comorbidity Index (KFI) in determining outcomes of posterior lumbar interbody fusion (PLIF) surgery. Methods: A retrospective analysis was conducted on 68 patients who underwent PLIF surgery performed by a single surgeon at a private hospital between 2022 and 2024. The male-to-female ratio was 3:2, with a minimum follow-up of one year. The KFI was applied to assess comorbidity burden. Results: Higher KFI scores correlated with poorer postoperative outcomes. Diabetes mellitus and ischemic heart disease emerged as significant predictors of adverse surgical outcomes. Conclusion: The KFI is a valuable tool for risk stratification in PLIF surgery. Patients with diabetes and ischemic heart disease may require closer perioperative management to optimize outcomes. Bang. J Neurosurgery 2025; 14(2): 85-89